2011
DOI: 10.1177/0961203311421798
|View full text |Cite
|
Sign up to set email alerts
|

The role of BsmI and FokI vitamin D receptor gene polymorphisms and serum 25-hydroxyvitamin D in Brazilian patients with systemic lupus erythematosus

Abstract: Vitamin D deficiency has been described in systemic lupus erythematosus (SLE). BsmI VDR (vitamin D receptor) gene polymorphism was associated with SLE in Asian patients. Studies in Brazilian populations have not been realized. A case-control study with 195 SLE patients and 201 healthy controls was conducted to investigate the influence of BsmI and FokI VDR gene polymorphisms on susceptibility to SLE. In addition, 25-hydroxyvitamin D [25(OH)D] was measured in SLE patients to evaluate possible associations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
65
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 57 publications
5
65
1
2
Order By: Relevance
“…This VDR isoform displayed higher transcriptional activity than the longer-type receptor (Arai et al, 1997). The role of the FokI SNP has recently been reinforced by Monticielo et al (2012). They found that vitamin D concentration was remarkably elevated in bearers of the TT (ff) genotype versus individuals having the CC (FF) genotype (Monticielo et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This VDR isoform displayed higher transcriptional activity than the longer-type receptor (Arai et al, 1997). The role of the FokI SNP has recently been reinforced by Monticielo et al (2012). They found that vitamin D concentration was remarkably elevated in bearers of the TT (ff) genotype versus individuals having the CC (FF) genotype (Monticielo et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…The role of the FokI SNP has recently been reinforced by Monticielo et al (2012). They found that vitamin D concentration was remarkably elevated in bearers of the TT (ff) genotype versus individuals having the CC (FF) genotype (Monticielo et al, 2012). The BsmI SNP may be associated with the different length polyadenylate sequence within the 3¢-untranslated region of the VDR gene (Uitterlinden et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, high frequency of the VDR (ATG) (f) allele was associated with a decrease in Th1 immune response (17). A previous study on the role of the FokI SNP demonstrated the presence of increased vitamin D levels in carriers of the TT (ff) genotype, as compared with carriers of the CC (FF) genotype (34). The presence of the VDR in normal endometrium and endometriotic implants has been demonstrated (35).…”
Section: Discussionmentioning
confidence: 99%
“…The function of BsmI and FokI SNPs on the biological effects of VDR have been extensively studied (18,(32)(33)(34). The BsmI polymorphism may change the length of the polyadenylate sequence in VDR transcript (18 significantly reduced the mRNA expression levels of VDR in carriers of the A (B) allele, as compared with subjects carrying the GG (bb) genotype (32).…”
Section: Discussionmentioning
confidence: 99%